A segurança contra incêndio em edificações de valor patrimonial: proposta de retrofit no centro cultural de São Francisco/PB - Vieira, Jéssica de Queiroz (2019)
This work presents the fire safety theme aimed to heritage buildings applied to retrofit at the São Francisco Cultural Center, located at João Pessoa / PB, currently in operation, but lacking in fire safety requirements, makes it liable to great damage, including to the cultural and tourist programming of the capital in case of related accident. In these buildings the risk of fire is higher than in other buildings, given the particularities of historic buildings, which have old, deficient electrical installations and few passive and active fire protection requirements, which makes a building vulnerable also to criminal acts. Through a bibliographic, documentary and normative review, important risk analysis aspects were identified for historical heritage and the necessary requirements to improve protection and thus support the development of the proposed fire safety retrofit of the San Francisco Cultural Center, combining the conditions established in the national regulations, Fire Department and heritage protection institutions in favor of the longevity of cultural collection. Finally, design decisions were developed to adapt the building to meet the smallest possible number of interventions, combining active protection requirements with passive protection requirements.